2017
DOI: 10.1037/pspp0000138
|View full text |Cite
|
Sign up to set email alerts
|

Big Five personality stability, change, and codevelopment across adolescence and early adulthood.

Abstract: Using data from 2 large and overlapping cohorts of Dutch adolescents, containing up to 7 waves of longitudinal data each (N = 2,230), the present study examined Big Five personality trait stability, change, and codevelopment in friendship and sibling dyads from age 12 to 22. Four findings stand out. First, the 1-year rank-order stability of personality traits was already substantial at age 12, increased strongly from early through middle adolescence, and remained rather stable during late adolescence and early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
161
5
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(192 citation statements)
references
References 87 publications
23
161
5
3
Order By: Relevance
“…The findings from the various studies are largely compatible with the maturity principle of personality development (Borghuis et al, ; Caspi, Roberts, & Shiner, ). This principle implies that, during adulthood, attributes that promote functioning in society and social relations tend to increase.…”
Section: Discussionsupporting
confidence: 67%
“…The findings from the various studies are largely compatible with the maturity principle of personality development (Borghuis et al, ; Caspi, Roberts, & Shiner, ). This principle implies that, during adulthood, attributes that promote functioning in society and social relations tend to increase.…”
Section: Discussionsupporting
confidence: 67%
“…Alpha was set at .05 for all analyses. As substantial differences in the degree and direction of changes in personality occur across adolescence till early adulthood (Borghuis et al, 2017), we controlled athletes' age in all our analyses. Further, to remove any possible confounds that training experience may have upon training behaviours, we also controlled athletes' training experience (i.e., years of receiving formal training).…”
Section: Main Analysesmentioning
confidence: 99%
“…We can gain some insight into the likely stability of effortful control in adolescence by examining the stability of conscientiousness, which shares many core features with effortful control, but is a broader construct that also includes orderliness, punctuality, and responsibility. Conscientiousness tends to be moderately-to-highly stable from age 12 to 22, with one-year test-retest correlations ranging from .45 to .90 (Borghuis et al, 2017;Klimstra et al, 2009). Taken together, these findings suggest that self-regulatory traits are moderately stable from childhood to young adulthood, but this issue merits further attention given the lack of finegrained longitudinal studies that have assessed effortful control across multiple developmental periods.…”
Section: Stability and Change In Self-regulatory Traitsmentioning
confidence: 84%
“…However, more recent research has found no statistically significant mean-level change in effortful control, or conscientiousness, across adolescence (Klimstra et al, 2009;Laceulle et al, 2012). Further complicating the situation, a growing body of research suggests that self-regulatory traits may even decrease during adolescence (De Fruyt et al, 2006;Borghuis et al, 2017;Leon-Carrion, Garcia-Orza, Perez-Santamaria, 2004;Soto et al, 2011;Van den Akker, Dekovic, Asscher, & Prinzie, 2014), leading some researchers to conclude that there is a temporary "self-regulatory dip" during adolescence (Soto & Tackett, 2015). Often referred to as the disruption hypothesis, it is thought that temporary decreases in socially desirable traits during adolescence are due to the profound biological, psychological, and social changes that most youth face during this time (Soto & Tackett, 2015).…”
Section: Stability and Change In Self-regulatory Traitsmentioning
confidence: 99%